Business Analysis Of Red Bean And All Grade Robusta Ground Coffee Processing: Study In In “Sintaro” Ground Coffee Companybusiness In Kabawetan Sub-District, Kepahiang Regency - Deva Yurita Ambarini; Irnad Irnad; Bambang Sumantri (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2020)
One of the ground coffee businesses in Kepahiang Regency is “Sintaro” operated from 2008 – Today and produces ground coffee through two material selection systems using all ground and red bean. The purpose of the present study was to estimate and analyze the revenue, value-added and marketing of the ground coffee processing which uses red bead and all grade bean. Value added was analysed using Hayami approach while revenue and marketing were analysed decriptively. Based on the research result, the revenue of ground coffee processing which uses red bead was Rp2,512,351/month or profitability level of 58 % while the revenue of ground coffee processing used all grade bean was Rp3,340,409 month profitability level of 42 %. The value-added of processing red bean was Rp 9,676 /Kg with value added ratio of 62% in a single production. The value-added of processing all grade bean was Rp2,834 /Kg with value added ratio of 46% in a single production. Red bean ground coffee marketing covered Bengkulu, Palembang, and Jakarta, with distribution percentages of 62 %, 26 %, and 12%, respectively. Meanwhile, all grade ground coffee covered Kepahiang Regency, Bengkulu, Lubuk Linggau and Lampung, with distribution percentages of 35 %, 28 %, 24 %, and 12 %, respectively.